19th Century Philadelphia Economy (Third Sector Social Economic Review, 2025)
The 19th century represents an important period for the American economy. Because the developments that enabled America, which gained its independence in 1783, to become the world's most powerful economy in the 20th century, emerged in the 19th century. One of the important centres where these developments took place is Philadelphia. The city's proximity to raw material resources, its serious production potential and its connection to the Atlantic Ocean via the Delaware River made Philadelphia stand out economically in this period. Thanks to these features, thousands of factories operating in different sectors such as locomotives, wagons, ships, hats, chemical products, aluminium, iron, sugar and textiles were established. In addition, railways, canals and motorways were built to facilitate the transport of the products produced in these factories and the raw materials of these products. Thanks to these investments, Philadelphia, whose trade volume increased in the 19th century, became a city exporting to South America, Europe, Africa and Asia. Thanks to all these developments, Philadelphia, which was one of the locomotive cities of the American economy especially in the early 19th century, actually has an important share in the USA becoming the most powerful economy in the world. In line with these explanations, the aim of this study is to analyse the general economic structure of the city of Philadelphia in the 19th century through transportation investments, production, industry and trade.
Keywords: Philadelphia; Railway; Production; Industry; Trade